CO2 absorption in a high efficiency silicon nitride mesh contactor - Constantinou, Achilleas; Barrass, Simon; Pronk, Frans; Bril, T.; Wenn, David A.; Shaw, John Edward Andrew; Gavriilidis, Asterios (My University, 2012)
CO 2 absorption in sodium hydroxide and diethanolamine solutions was investigated in a silicon nitride mesh contactor. Mesh contactors allow two phases to come into direct contact with each other, for the purpose of mass transfer between them without dispersing one phase into the other. The 1μm thick silicon nitride mesh, containing a high density of uniform 0.5μm pores, facilitated the stabilization of the gas liquid interface at its pores. Experimental results were obtained for 2M NaOH or 2M DEA solutions and 20% vol. CO 2/N 2 inlet concentrations, with a fixed inlet molar ratio CO 2:NaOH of 0.4. Results showed that 23% of the CO 2 contained in the inlet stream was removed within 0.5s experimental gas residence time. CO 2 removal efficiency was higher when NaOH was used for absorption as compared to DEA. Experiments were also conducted with different mesh/membrane contactors: a PTFE membrane (thickness 20μm, pore size 0.5-5μm), a Ni-25 mesh (thickness 25μm, pore size 25μm) and a Ni-5 mesh (thickness 5μm, pore size 5μm). The silicon nitride mesh demonstrated the best performance primarily due to its small thickness.
Keywords: Carbon dioxide absorption; Microchannel; Multiphase contactor; Membrane; Microreactor